The Effect of Core Stability Exercises on The Accuracy of Jump Serve Volleyball Athletes - Rizal Hidayat; Dikdik Zafar Sidik; Mulyana (Journal of Physical Education Health and Sport, 2025)
This study aimed to investigate the effect of core stability exercises on the accuracy of jump serves in volleyball athletes. The research was conducted using a quasi-experimental design with a two-group pre-test and post-test approach. The participants consisted of volleyball athletes from the Star Sport Rancaekek Club, who were divided into an experimental group and a control group. The experimental group received a five-week core stability training program, while the control group continued their regular training routine. Jump serve accuracy was measured using the AAHPER Serving Accuracy Test. Data analysis showed that the experimental group demonstrated a significant improvement in serve accuracy compared to the control group. These findings indicate that core stability training effectively enhances body balance, postural control, and coordination—key components in executing accurate jump serves. The results highlight the importance of incorporating core stability exercises into volleyball training programs, especially for improving specific technical skills. This study contributes to the field of sports coaching by offering practical insights into effective methods for developing skill-based performance in young volleyball athletes.